THE ICHNOFOSSIL GENUS PARADICTYODORA OLIVERO, BUATOIS & SCASSO(2004) FROM THE PLIOCENE OF THE NORTHERN APENNINES, ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
The ichnospecies Paradictyodora flabelliformis (D¡¦Alessandro & Fürsich) is reported for the first time from the Pliocene ¡§Argille Azzurre Formation¡¨ of Northern Italy. The horizon has an older age and is deeper than the shallow-water protected shoreface environment where the type specimens have been found. A narrow tubular structure exceptionally preserved on the specimen studied possibly supports the tellinid bivalve model instead of the Arenicola model for the origin of the trace fossil.
Keywords: Fodinichnion; Paradictyodora; Pliocene; Northern Italy